2015
DOI: 10.1103/physrevd.91.124055
|View full text |Cite
|
Sign up to set email alerts
|

Magnetosphere of a Kerr black hole immersed in magnetized plasma and its perturbative mode structure

Abstract: This work studies jet-like electromagnetic configurations surrounding a slowly-spinning black-hole immersed in a uniformly magnetized force-free plasma. In the first part of this work, we present a family of stationary solutions that are jet-capable. While these solutions all satisfy the forcefree equations and the appropriate boundary conditions, our numerical experiments show a unique relaxed state starting from different initial data, and so one member of the family is likely preferred over the others. In t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 62 publications
(75 reference statements)
4
27
2
Order By: Relevance
“…In this work, we revisit this problem guided by high accuracy solutions, again obtained by evolving the general-relativistic force-free equations. We confirm previous results regarding the structure of the electromagnetic fields, the angular velocity, and luminosity from these solutions [2,[4][5][6][7]. However, we also focus on some new aspects.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this work, we revisit this problem guided by high accuracy solutions, again obtained by evolving the general-relativistic force-free equations. We confirm previous results regarding the structure of the electromagnetic fields, the angular velocity, and luminosity from these solutions [2,[4][5][6][7]. However, we also focus on some new aspects.…”
Section: Introductionsupporting
confidence: 90%
“…Here we study a prototypical setup that exhibits the Blandford-Znajek mechanism: a spinning BH immersed in a uniformly magnetized plasma. Starting with [2], there have been a number of studies of this problem using numerical evolutions of the generalrelativistic equations of FFE [3][4][5][6][7]. These have found that the solution relaxes to a stationary BH jet configuration with a Poynting flux powered by the rotational energy of the BH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But for the vertical field lines, their exists only one LS, which is insufficient for determining two eigenfunctions. In this case, many solutions are expected [15,16], but the many-solutions scenario is in conflict with several previous FFE simulations [5,[17][18][19][20][21][22]. To explain the discrepancy on the uniqueness of uniform field solution, Pan et al [23,24] proposed that the two eigenfunctions are not independent; instead, they are related by the radiation condition at infinity, which is formulated asÊ θ =B φ , withÊ θ andB φ being the θ component of electric field and φ component of the magnetic field measured by zero-angularmomentum-observers, respectively.…”
Section: A Solution Uniqueness and Radiation Conditioncontrasting
confidence: 65%
“…But for other magnetic field configurations, there is no such good agreement, e.g., different approaches do not even reach a consensus on the solution uniqueness for the uniform field configuration. Several force-free electrodynamics (FFE) simulations [5,[17][18][19][20][21][22] have been done and the BH magnetospheres in these simulations all settle down to a steady state with similar final field configuration, which is an indicator for solution uniqueness.…”
Section: Introductionmentioning
confidence: 99%